2023
DOI: 10.21037/atm-23-1517
|View full text |Cite
|
Sign up to set email alerts
|

Anti(angiogenic) food components: can be a major source of bias in the investigation of angiogenesis inhibitors

Reza Rastmanesh,
Abdalla Bowirrat,
Ashim Gupta
et al.

Abstract: Background Natural and diet-derived angiogenesis inhibitors/promotors are widely found in diets. These compounds can in several ways impact the results of oncological research of angiogenesis inhibitors. Methods We very briefly overview some of the most important examples to show how these compounds can create a bias in current research of cancer. Implications of this expert opinion cover similar angiogenesis-related diseases. Results Signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…These differences in the results might be partly due to the higher efficacy of nano-curcumin, like many other treatments, to change cardiometabolic risk factors when the baseline values are impaired. Moreover, Rastmanesh et al recently showed that the intra-individual differences in terms of dietary intake and food processing techniques result in differential bioactivity and bioavailability of many antioxidants including curcumin and curcuminoids [ 62 ]. They also added that even randomization protocols or using cross-over or parallel designs cannot eliminate this source of bias [ 62 ].To our knowledge, dietary intakes of curcumin and curcuminoids have not been assessed in previous studies as well as the current trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences in the results might be partly due to the higher efficacy of nano-curcumin, like many other treatments, to change cardiometabolic risk factors when the baseline values are impaired. Moreover, Rastmanesh et al recently showed that the intra-individual differences in terms of dietary intake and food processing techniques result in differential bioactivity and bioavailability of many antioxidants including curcumin and curcuminoids [ 62 ]. They also added that even randomization protocols or using cross-over or parallel designs cannot eliminate this source of bias [ 62 ].To our knowledge, dietary intakes of curcumin and curcuminoids have not been assessed in previous studies as well as the current trial.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Rastmanesh et al recently showed that the intra-individual differences in terms of dietary intake and food processing techniques result in differential bioactivity and bioavailability of many antioxidants including curcumin and curcuminoids [ 62 ]. They also added that even randomization protocols or using cross-over or parallel designs cannot eliminate this source of bias [ 62 ].To our knowledge, dietary intakes of curcumin and curcuminoids have not been assessed in previous studies as well as the current trial. Serum concentrations of these compounds have not been evaluated, either; while the effects of these compounds are greatly influenced by their concentrations.…”
Section: Discussionmentioning
confidence: 99%